Does trade liberalization enhance income growth and equity in Zimbabwe?: the role of complimentary policies - Bautista, Romeo M.; Lofgren, Hans; Thomas, Marcelle (International Food Policy Research Institute, 1998)
Using an agriculture-focused CGE model for Zimbabwe with 1991 as base period, this paper examines quantitatively the income and equity effects of trade liberalization in isolation and in conjunction with potentially complementary changes in fiscal and land policies. Trade policy reform alone (dismantling of import and foreign exchange controls, and reduction of import taxes to a low uniform rate) is shown to increase aggregate disposable household income significantly. However, the least income gain accrues to smallholder farm households, which account for about four-fifths of the poor in Zimbabwe, so the equity impact is unfavorable. Concurrent implementation with specific changes in government expenditure and tax policies and two alternative stylized land redistribution schemes yields differing outcomes in terms of aggregate household income growth and its distribution.